2017
DOI: 10.1016/j.biocontrol.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of grapevine aerial and root pathogens by Paenibacillus sp. strain B2 and paenimyxin in vitro and in planta

Abstract: h i g h l i g h t s Paenibacillus sp. strain B2 and its antagonistic factor paenimyxin control grapevine pathogens. The bio-control effects are active against aerial or root pathogens in vitro or in planta. Paenimyxin acts as a biopesticide against the oomycete but does not trigger plant defense. Paenibacillus sp. strain B2 can induce plant defense gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The strain B2 inoculated with the vesicular-arbuscular mycorrhizal fungus Glomus mosseae , was found to produce peptide paenimyxin that significantly reduced the mobility of P. viticola zoospores and mycelium growth of B. cinerea . When an extracted peptide was applied by spraying before the infection, it was not effective, suggesting a direct action of paenimyxin (Hao et al, 2017 ). Endophytic bacterial strain Pseudomonas fluorescens PTA-CT2, isolated from grapevine stems, reduced downy mildew disease by induction of systemic resistance in pre-infection applications on greenhouse-grown plants (Lakkis et al, 2019 ).…”
Section: Disease Managementmentioning
confidence: 99%
“…The strain B2 inoculated with the vesicular-arbuscular mycorrhizal fungus Glomus mosseae , was found to produce peptide paenimyxin that significantly reduced the mobility of P. viticola zoospores and mycelium growth of B. cinerea . When an extracted peptide was applied by spraying before the infection, it was not effective, suggesting a direct action of paenimyxin (Hao et al, 2017 ). Endophytic bacterial strain Pseudomonas fluorescens PTA-CT2, isolated from grapevine stems, reduced downy mildew disease by induction of systemic resistance in pre-infection applications on greenhouse-grown plants (Lakkis et al, 2019 ).…”
Section: Disease Managementmentioning
confidence: 99%
“…Bacteria of the genus Paenibacillus comprise bacterial species that have been reported as symbionts of plants such as corn, squash and rice, and it has been identified that they can promote their growth [17,18]. They are widely distributed around the globe.…”
Section: Resultsmentioning
confidence: 99%
“…strain B2 secretes the peptide paenimyxin, which acts as a biopesticide against different grapevine pathogens. Hao et al (2017) showed that Paenibacillus sp. strain B2 can inhibit the development of P. viticola and B. cinereain vitro and affects the activity of the ectoparasitic nematode Xiphinema indexin vitro and in planta .…”
Section: Defense Against Biotic Agentsmentioning
confidence: 99%